The Creation of Effective Property Rights - Grossman, Herschel I (American Economic Review, 2001)
Traditionally, general-equilibrium models have taken effective property rights to be given and have been concerned only with analyzing the allocation of resources among productive uses and the distribution of the resulting product. But, this formulation of the economic problem is incomplete because it neglects that the appropriative activities by which people create the effective property rights that inform allocation and distribution are themselves an alternative use of scare resources. This paper develops two canonical general-equilibrium models of resource allocation and income distribution that allow for the allocation of time and effort to the creation of effective property rights to valuable resources. In one model the valuable resources are initially in common pool. In the other models the analysis reveals how the amount of time and effort that agents allocate to the creation of effective property rights, on the technology of production, and on the scale of the economy. The paper also analyses the security of initial claims to valuable resources and speculates about why initial claims are perfectly secure.